Gender, Household Food Security and Neoliberal Decimation of the Grain-Producing Peasantry in Zimbabwe - Tekwa, Newman; Tekwa, Happymore (Springer, Cham, 2022)
With over half of the Zimbabwean population now facing food hunger, this could be juxtaposed to the 1980s’ dirigiste period when the state boosted peasant maize production (as a proportion of national maize output) from 3.6% in 1979/80 to 35.6% in 1984/85. Since then, though interspersed with brief periods of heavy state involvement in the 2000s, Zimbabwe has undergone three decades of economic liberalisation from a Structural Adjustment Programme (SAP) in the early 1990s to the current Transition Stabilisation Programme (TSP). The gendered effects of decades of agricultural market liberalisation on peasant households in the country remain inadequately documented and analysed. In this chapter, we first consider the extent to which the shift from dirigisme to liberalisation affected integration, efficiency and competitiveness in the agricultural sector. We examine the distribution of benefits of market liberalisation across different scales of agricultural production in addition to interrogating how female peasants have fared in these economic restructuring processes relative to men, primarily in relation to food security. We argue that liberalisation negatively impacted peasant maize production and curtailed the dual role of peasant households, leading to gender-differentiated knock-on effects for household food security. This highlights the crucial role of the state in ensuring national and household food sufficiency.